Adoption of IoT in Agriculture - Firdaus, Muhammad Ammar; Ismail, Siti Norziah (Research in Management of Technology and Business, 2025)
One of Malaysia's top dairy companies, Farm Fresh, has harnessed the Internet of Things (IoT) to improve efficiency and streamline its agricultural operations. Farm Fresh desires to raise the bar for sustainable and effective dairy production by incorporating IoT technology into every facet of farming, from animal management to crop monitoring. Farm Fresh has been able to maximize resource use, save waste, and boost productivity throughout its operations thanks to the implementation of IoT. The firm has been able to provide consumers with high-quality dairy products while also promoting sustainable agricultural techniques through the utilization of data and technology. IoT-powered smart agricultural solutions will be essential to supplying the growing worldwide need for food while fostering environmental sustainability as the world's population continues to rise. Other farming businesses hoping to embrace the future of farming and spur innovation in the sector might learn from Farm Fresh's effective IoT integration.